PEMBERIAN PAKAN ALAMI YANG BERBEDA PADA IKAN BLACK GHOST (Apteronotus albifront) - Fahrul Rozi; Rusliadi Rusliadi; Iskandar Putra (Berkala Perikanan Terubuk, 2017)
The study was conducted from 1 th of March to 16 th April 2017 at the Center for Research and Cultivation of Ornamental Fish (BRBIH), Depok West Java Province. Which aims to determine the best natural food for growth and survival of Black Ghost fish (Apteronotus albifront). The method used was experimental method with Randomized Complete Design, with 3 treatment levels and 4 replications, ie P1 (Tubifex sp), P2 (Moina sp), P3 (Culex sp). The maintenance container used was an aquarium of 40 cm x 30 cm x 30 cm (24 liters of water), with a stagnant system. Fish used as 50fish/aquaria, fish fed 3 times a day. Growth sampling was done at the beginning and every 10 days. Measurement of water quality parameters include physics and chemistry ie Temperature, pH, DO, Ammonia, Nitrite and Nitrate. The results showed that feeding ofTubifex sp gave the best result of absolute long growth of 4.4 cm, absolute weight growth 1.38 g, spesific growth rate of 5.3% , survival rate 74%.